Pengaruh Musik Terhadap Beban Kerja Mental Pekerja Batik Tulis Dan Cap Di Batik Putra Laweyan - Caprianingsih, Farinda Ewin, Etika Muslimah, S.T., M.M., M.T, Much. Djunaidi, S.T., M.T (2015)
Batik Putra Laweyan is one of the home industry engaged in the manufacture of batik cloth. The company produces batik products, batik and batik. Like most home industry, all plant processes are still done manually. Coupled with the demands of the target high enough to make employees have a high pressure, in addition to the work performed manually and the pressure of targets high enough, kind of monotonous work, batik work can also lead to boredom. This raises the mental workload on employees. The purpose of this study was to determine differences in the mental burden of employees at work without listening to music and mental workload of employees at work by listening to music, as well as differences in the mental workload that workers batik and batik workers. In this study, the method used is NASA TLX method is to determine the mental workload on workers batik and batik. The number of respondents who would learn in our study totaled 9 employees. The study was conducted in Laweyan Putra Batik home industry in the process of making batik and batik. Nasa TLX score calculation results in workers cutting the fabric and fabric design on the initial conditions are 81 and 64 treatment conditions, workers mencanting batik on the initial conditions and the conditions of the treatment is 82 is 59, workers batik coloring on the initial conditions and the conditions of treatment was 81 69 , workers giver motif stamp on the initial conditions is 86 and the condition of the treatment is 62, workers pencanting batik in the initial conditions 83 and 57 treatment condition, batik dyeing workers at the initial condition is 77 and the condition perakuan is 57. It can be seen that music can reduce the burden of mental work at home industry experienced workers in Batik Putra Laweyan. Keywords: Nasa TLX, Mental Workload, Music